2022
DOI: 10.1097/phm.0000000000002127
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in Academic Physiatry

Abstract: Environmental scans determine trends in an organization's or field's internal and external environment. The results can help shape goals, inform strategic decision making, and direct future actions. The Association of Academic Physiatrists convened a strategic planning group in 2020, composed of physiatrists representing a diversity of professional roles, career stages, race and ethnicity, gender, disability status, and geographic areas of practice. This strategic planning group performed an environmental scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…For example, an environmental scan conducted by the Association of Academic Physiatrists concluded that many creative recruiting strategies are imperative to sustaining the workforce of committed physiatrists of excellent quality. 1 Many who graduate from medical school have yet to hear of PM&R, and very few find their way to the field. The Association of Academic Physiatrists observed that compared with other specialties, these few graduates entering physiatry "are less racially and ethnically diverse."…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…For example, an environmental scan conducted by the Association of Academic Physiatrists concluded that many creative recruiting strategies are imperative to sustaining the workforce of committed physiatrists of excellent quality. 1 Many who graduate from medical school have yet to hear of PM&R, and very few find their way to the field. The Association of Academic Physiatrists observed that compared with other specialties, these few graduates entering physiatry "are less racially and ethnically diverse."…”
mentioning
confidence: 99%
“…The Association of Academic Physiatrists observed that compared with other specialties, these few graduates entering physiatry "are less racially and ethnically diverse." 1 Currently, in the United States, there is an evident lack of medical schools that require a PM&R rotation and many that lack an adequate rehabilitation education curriculum. 2 A survey of 2067 medical students similarly found that of those that discover the field before graduation, underrepresented minorities are far less likely to be present.…”
mentioning
confidence: 99%
See 3 more Smart Citations